Professional issues for the Nigerian veterinarian in the twenty-first century (2005)
The imperative of enhanced professionalism of veterinary practice in Nigeria in a technologically advanced and sophisticated 21st century is discussed. The concept of professionalism, the qualities of a professional, an overview of expectations from the Veterinary Council of Nigeria, Nigerian Veterinary Medical Association, Nigerian veterinary educational institutions, public sector veterinarians, private sector veterinarians and individuals in enhancing professionalism of veterinary practice in Nigeria are enumerated. One of the challenges that will face the Nigerian veterinarian as we enter the twenty-first century is the response to the demands of an increasingly sophisticated Nigerian society. Definitely, the 21st century will be characterized by increased application of science and technology and of higher taste, values and expectation from clients and consumers. How does the veterinarian respond appropriately to this? It is only by enhanced professionalism by veterinary practitioners that the profession can meet these imminent challenges. This paper highlights the areas where increased professionalism are called for, and the roles and functions of different veterinary groups in meeting these challenges.